IMPACT ON MATERNITY LEAVE AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE AT MAIN BRANCH OF BNI 46 MANADO - Poeng, Meilany .; Pangemanan, Sifrid S; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Becoming a mother, being pregnant, giving birth and taking care of the child, in case of this situation, woman must take maternity leave. This purpose of this research is to know how the maternity leave and career development influence on employee performance at BNI branch Manado. This research is qualitative analysis interview, the population in this research is woman employee who have took maternity leave at BNI branch Manado, and the sample using purposive sampling. The variables used in this research were taken from the literature to determine the relation between maternity leave, career development on employee performance. The data gathered through interview with the informants. The result showed that 40% of total informants explained that there were difficulties and uncomfortability during their job while taking role as mother at the same period, while the 60% feels no difficulties. The conclusion in this research is maternity leave in BNI branch Manado did not cause employee performance to decline, since the employee who took maternity leave in this company are experienced in terms of skill and motherhood experience. This research recommends BNI branch Manado should maintain and improve the good sign of objectivity and support toward employee who take maternity leave.Â Keywords: maternity leave, employee performance, career development